Die Mission des "American Board" in Syrien im 19. Jahrhundert: Implikationen eines transkulturellen Dialogs - Zeuge-Buberl, Uta (Missionsgeschichtliches Archiv, 2016)
The focus of this study is the “Syria Mission”, directed by the Protestant missionary society American Board of Commissioners for Foreign Missions (ABCFM) from 1819 to 1870 in the Ottoman province of Syria, operating mainly within the territory of present-day Lebanon. The analysis of the cultural transfer between the Ottoman Empire and the United States of America undertaken in this study focuses on four relevant protagonists, whose contributions have not yet been sufficiently explored in missiological studies: The missionaries Eli Smith and Cornelius Van Dyck as well as the Syrian Protestants Butrus al-Bustani and John Wortabet. As a result, the Syria Mission of the ABCFM demonstrates how two different cultures met in a so called contact zone in the mission field and how these dialogue partners, despite many conflicts and disagreements, succeeded in contributing towards a fruitful dialogue.Im Zentrum der Untersuchung steht die Syrienmission der protestantischen Missionsgesellschaft American Board of Commissioners for Foreign Missions (ABCFM), die sich von 1819 bis 1870 in der Osmanischen Provinz Syrien, d.h. auf dem Gebiet des heutigen Libanon, etablierte. Die Analyse des kulturellen Austausches zwischen dem Osmanischen Reich und den Vereinigten Staaten von Amerika setzt bei vier wichtigen Protagonisten an, die in der bisherigen missionsgeschichtlichen Forschung nicht ausführlich bzw. gar nicht Beachtung fanden: Die Missionare Eli Smith und Cornelius Van Dyck sowie die syrischen Protestanten Butrus al-Bustani und John Wortabet. Die Syrienmission des ABCFM ist ein Beispiel dafür, wie zwei verschiedene Kulturen in der sogenannten contact zone der Missionsstationen aufeinander trafen und trotz Konflikten und Meinungsverschiedenheiten zu einem fruchtbaren Dialog gelangen konnten